The Impact of Decree 046 of 2024 on the Liability Regime of Administrators in Colombia - Henao Beltrán, Lina Fernanda (2024)
In this article, the author seeks to carry out an exhaustuve analysis regarding the impact of D.S. 046 on the liability regime of directors within Colombian legislation, thus specifying the areas of the duties of diligence, good faith and coporate loyalty. Furthermore, it’s mentioned that said norm, by incorporating the rule of deference to business criteria, grants greater autonomy when making decisions in favor of the interests of the company.